2021
DOI: 10.1111/jfpp.15465
|View full text |Cite
|
Sign up to set email alerts
|

High pressure processing of licorice drink with respect to quality characteristics, microbial inactivation, and shelf‐life extension

Abstract: Liquorice (Glycyrrhiza glabra) is one of the oldest and well known plants in ancient China, Egypt, and Rome and have been used in medical, food, and cosmetic industries owing to its saponins, flavanones, flavonoids, amines, glucose, sucrose, amino acids, gums, essential oils, and starch present in its roots (Liu, Chen, et al., 2016).Glycyrrhizic acid up to 50 times as much sweet as sucrose consisting of one molecule of glycyrrhetinic acid, and two molecules of glucuronic acid is the major compound in licorice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
(42 reference statements)
0
5
0
Order By: Relevance
“…Ergün et al reported that the sugar amounts of blueberry and mulberry sherbets decreased significantly after 60 days of storage . Evrendilek et al did not determine a significant change in organic acid values (acetic, formic, and fumaric acid) as a result of the 25-day storage of licorice beverages with hydrostatic pressure …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ergün et al reported that the sugar amounts of blueberry and mulberry sherbets decreased significantly after 60 days of storage . Evrendilek et al did not determine a significant change in organic acid values (acetic, formic, and fumaric acid) as a result of the 25-day storage of licorice beverages with hydrostatic pressure …”
Section: Resultsmentioning
confidence: 99%
“… 56 Evrendilek et al did not determine a significant change in organic acid values (acetic, formic, and fumaric acid) as a result of the 25-day storage of licorice beverages with hydrostatic pressure. 57 …”
Section: Resultsmentioning
confidence: 99%
“…Shelf-life studies conducted with the optimum HHP conditions resulted in a 25-d storage compared with the 2-to-7-d shelf life of the control samples at 4 and 22 • C [17].…”
Section: Discussionmentioning
confidence: 98%
“…They evaluated the samples for appearance (cloudiness-clarity, color intensity, dullness-shininess, and particle distribution) and then for flavor-aroma. Finally, the panelists tasted the samples in order to measure changes in important sensory attributes, such as a sour taste, bitter taste, sweetness, hardaliye taste, and aftertaste [17]. Hardaliye has a very attractive dark red color, which fades away, revealing an unpleasant brownish color with an extended storage and increased temperature.…”
Section: Sensory Analysesmentioning
confidence: 99%
“…NTP may be integrated with antimicrobial compounds or moderate heating to achieve the desired results (H. Lee, Choi, Kim, Kim, Lee, & Lee, 2021 ). HPP and PEF have been extensively studied and effectively marketed for the non-thermal inactivation of micro-organisms ( Akdemir Evrendilek et al, 2021 , Soltanzadeh et al, 2020 ).…”
Section: Non-thermal Processing (Ntp) In the Circular Economymentioning
confidence: 99%